2017
DOI: 10.1111/jpc.13507
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of paracetamol versus ibuprofen administration in febrile children: A systematic literature review

Abstract: There is little evidence supporting the superior efficacy of paracetamol or ibuprofen in the treatment of fever in children with indications that both drugs are equally effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
(51 reference statements)
0
6
0
3
Order By: Relevance
“…Ibuprofen and paracetamol are the only antipyretics recommended in febrile children, basing on abundant evidence of their efficacy and safety profile. A recent systematic literature review (7), including eight studies on 1,632 children, concluded that both drugs are equally effective in reducing fever and discomfort in children. Other literature reports, including two meta-analyses (8, 9), observed a similar safety profile (10).…”
Section: Introductionmentioning
confidence: 99%
“…Ibuprofen and paracetamol are the only antipyretics recommended in febrile children, basing on abundant evidence of their efficacy and safety profile. A recent systematic literature review (7), including eight studies on 1,632 children, concluded that both drugs are equally effective in reducing fever and discomfort in children. Other literature reports, including two meta-analyses (8, 9), observed a similar safety profile (10).…”
Section: Introductionmentioning
confidence: 99%
“…Level 3; relieves discomfort in febrile illness (down-graded because SR only included 3 studies and only 44% of children showed less discomfort compared to ibuprofen 69%); (SR)[88] Sole recommended antipyretic 9No published evidence comparing ibuprofen and paracetamol shows a superior effect or safety profile of paracetamol (Review appraisal)[90] As the 1st line antipyretic 17 Level 1; review appraisal[90] SR[89] As 2nd line antipyretic after ibuprofen/physical methods 1 Level 2; RCT, meta-analysis[91] Dose determination Follow doctor's advice 6 Level 1; dose by weight and/or age; SR[89] https://doi.org/10.1371/journal.pone.0245815.t001…”
mentioning
confidence: 99%
“…reviewed 3023 articles related to oral paracetamol and ibuprofen in pediatric fever management, and in 6 out of 8 studies meeting the criteria, ibuprofen proved somewhat, though not significantly, more effective than paracetamol in reducing fever in children. [ 21 ] When it comes to our study, fever decline between baseline and 60 min remained unchanged in both groups, and we concluded that ibuprofen and paracetamol could be antipyretic equals. From this perspective, the results obtained in our study seem to validate the data reported in Narayan et al .…”
Section: Discussionmentioning
confidence: 48%